The importance of outpatient unit in the diagnosis and treatment of HIV (Research, Society and Development, 2022)
The prevalence of HIV infection remains high in the world and individuals with the virus receive care at the Specialized Care Service for HIV/AIDS, provided by the Unified Health System. Thus, the present study aimed to carry out a review, in order to demonstrate the routine and methodologies used by outpatient units specializing in diagnosing and treating patients with HIV. For this, an integrative review was carried out, with inclusion criteria that covered articles published between the years 2018 and 2022, in Portuguese and English. Fourteen scientific articles were selected, in addition to dissertations and manuals from the Ministry of Health for the elaboration of the results. The data revealed that the outpatient units are responsible for the reception and medication adherence of patients. Antiretroviral therapy, when used properly, reduces the amount of viral in the blood, resulting in the prevention of opportunistic diseases, providing the patient with well-being and quality of life. It is concluded, then, about the importance of these units in the scope of public health, both in the prevention and in the therapeutic treatment of the HIV virus, with the intention of attenuating its transmission.